Pengaruh Kualitas Pelayanan terhadap Volume Penjualan pada UMKM Mie Cihuy karawang - Muharam, Said; Isyanto, Puji; Sumarni, Neni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
"Mie Cihuy" which is located in Karawang is one of the SMEs engaged in the restaurant sector. "Mie Cihuy" has lasted more than 20 years and is believed to have good service quality, according to the results of this study which show that buyers perceive the service as good. This study aims to determine how much influence service quality has on the sales volume of "Mie Cihuy" UMKM. This study uses validity and reliability tests to determine how valid and reliable the respondents are in assessing the variables in this study. As well as a service quality scale that aims to determine service quality with indicators of tangibles, reliability, responsiveness, assurance and empathy dimensions using quantitative methods. The data analysis technique used was simple regression analysis using SPSS version 26 software with a total of 46 respondents. Based on the results of the service quality scale, it shows that respondents agree about service quality and sales volume at Mie Cihuy UMKM. Simple regression analysis shows that service quality has a significant effect on the sales volume of Mie Cihuy UMKM. Adjust R Square results show a value of 0.653, this means that 65.3% of sales volume is influenced by service quality and as much as 34.7% is influenced by variables that are not present in this regression model. Keywords: Service Quality, Sales Volume, SMEs